Are Thyroid Hormone and Tumor Cell Proliferation in Human Breast Cancers Positive for HER2 Associated? - Iordanis Mourouzis; Alexandros Tzovaras; Basil Armonis; Alexandros Ardavanis; Maria Skondra; John Misitzis; Demetrios Pectasides; Constantinos Pantos (International Journal of Endocrinology)
Objective. This study investigated whether thyroid hormone (TH) levels are correlated to cell proliferation (Ki67), in euthyroid breast cancer patients. Design and Methods. 86 newly diagnosed breast cancer patients with estrogen receptor (ER) positive tumors, who referred for surgery, were included in the study. Results. FT3, FT4, and TSH were within normal range. No correlation was seen between Ki67 and FT3 (r=-0.17, P=0.15), FT4 (r=-0.13, P=0.25), or TSH (r=-0.10, P=0.39) in all patients studied. However, subgroup analysis showed that, in HER2(+) patients, a negative correlation existed between FT3 levels and Ki67 (r=-0.60 and P=0.004) but not between Ki67 and FT4 (r=0.04 and P=0.85) or TSH (r=-0.23 and P=0.30). In HER2(−) patients, there was no significant correlation between Ki67 and FT3 (r=-0.06, P=0.67), FT4 (r=-0.15, P=0.26), or TSH (r=-0.09, P=0.49). Phospho-p44/total p44 ERK levels were found to be increased by 2-fold in HER2(+) versus HER2(−) tumors. No difference was detected in phospho-p42/total p42 ERK levels. Conclusions. TH profile is not altered in patients with newly diagnosed breast cancer. However, FT3 levels, even within normal range, are negatively correlated with cell proliferation in HER2(+) breast cancer tumors. This response may be due to the interaction between ERK and TH signaling.